CAMPUR KODE PEMAKAIAN BAHASA INDONESIA PADA WACANA IKLAN - I Nengah Mileh (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2020)
This study is entitled "Mixing Indonesian Language Codes in Advertising Discourse". The use of Indonesian in discourse advertisements has taken place in another language, namely local languages and foreign languages. This study examines the factors that cause code mixing, the types and forms / forms of code mixing, and the social meaning that is caused by the code mixing. The study uses the method of observation (observation) and data collection techniques, descriptive qualitative methods used in analyzing data, and informal methods used to collect the results of the analysis. In this study found two kinds of mixed codes, namely mixed codes into local languages (Balinese and Javanese) and mixed codes out of English. The shape and form of the code that is found is a mixture of code in the form of words, namely nouns, verbs, adjectives and adverbs. In addition to the form of words also found a mixture of code in the form of phrases, namely nominal phrases, verbal phrases, and prepositional phrases. There are two causes of code mixing in discourse, namely intralinguistic factors and extralinguistic factors. The code mixing events in the discourse are related to the language and social background, so that social meaning arises due to the code mixing behavior. Social meaning that emerges, shows more educated, shows social class, shows creativity, and shows the practical and regionalism.